Techniques for adaptive control - VanDoren, Vance J. (Amsterdam ; Boston : Butterworth-Heinemann, 2003)
"Techniques for Adaptive Control" compiles chapters from a team of expert contributors that allow readers to gain a perspective into a number of different approaches to adaptive control. In order to do this, each contributor provides an overview of a particular product, how it works, and reasons why a user would want it as well as an in depth explanation of their particular method. This is one of the latest technologies to emerge in the instrumentation and control field. These latest control methodologies offer a means to revolutionize plant and process efficiency, response time and profitability by allowing a process to be regulated by a form of rule-based AI, without human intervention. Rather than the common academic-based approach that books on this subject generally take, the contributions here outline practical applications of adaptive control technology allowing for a real look inside the industry and the new technologies available.; Written by a team of contributors from the industry's best-known product manufacturers and software developers, the book provides real insight into new technologies available in the industry, and outlines practical applications of adaptive control technology.
Adaptive Tuning Methods of the Foxboro I/A System; The Exploitation of Adaptive Modelling in the Model Predictive Control Environment of Connoisseur; Adaptive Predictive Regulatory Control with BrainWave; Model-Free Adaptive Control; Expert-Based Adaptive Control -- ControlSoft's INTUNE Adaptive and Diagnostic Software; KnowledgeScape, an Object-oriented Real-time Adaptive Modeling and Optimization Expert Control System for the Process Industries.
Includes bibliographical references and indexes.
Keywords: Adaptive control systems; Electronic books